2022
DOI: 10.1002/advs.202104579
|View full text |Cite
|
Sign up to set email alerts
|

One‐Step MOF‐Templated Strategy to Fabrication of Ce‐Doped ZnIn2S4 Tetrakaidecahedron Hollow Nanocages as an Efficient Photocatalyst for Hydrogen Evolution

Abstract: Achieving structure optimizing and component regulation simultaneously in the ZnIn2S4‐based photocatalytic system is an enormous challenge in improving its hydrogen evolution performance. 3D hollow‐structured photocatalysts have been intensively studied due to their obvious advantages in solar energy conversion reactions. The synthesis of 3D hollow‐structured ZnIn2S4, however, is limited by the lack of suitable template or synthesis methods, thereby restricting the wide application of ZnIn2S4 in the field of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(42 citation statements)
references
References 57 publications
0
34
0
Order By: Relevance
“…This heterogeneous microreactor can strengthen the electron trapping ability, and thus requires more electrons and protons to generate CH 4 . Metal–organic frameworks (MOFs) with fascinating topology, large pore volume, and chemical adjustability provide an excellent platform to fabricate the semiconductors with a microcapsule structure 12,13 including metal oxides, 14 metal sulfides, 15 layered double hydroxides (LDHs) by using ion-exchange or solvothermal method, 16 which enables the encapsulation of numerous nanoparticles or nanosheets on the capsules. For instance, Bibi et al found that thioacetamide (TAA) can decompose MIL-125 to form TiO 2 /CdS capsules after the post-solvothermal method, which exhibited enhanced photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…This heterogeneous microreactor can strengthen the electron trapping ability, and thus requires more electrons and protons to generate CH 4 . Metal–organic frameworks (MOFs) with fascinating topology, large pore volume, and chemical adjustability provide an excellent platform to fabricate the semiconductors with a microcapsule structure 12,13 including metal oxides, 14 metal sulfides, 15 layered double hydroxides (LDHs) by using ion-exchange or solvothermal method, 16 which enables the encapsulation of numerous nanoparticles or nanosheets on the capsules. For instance, Bibi et al found that thioacetamide (TAA) can decompose MIL-125 to form TiO 2 /CdS capsules after the post-solvothermal method, which exhibited enhanced photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] However, the poor visible light absorption of photocatalysts limits solar light energy utilization and thus restricts their practical applications. The sulfides, such as CdS, ZnS, ZnIn 2 S 4 , [6][7][8] etc., have been mainly used as visible-light photocatalytic materials. ZnIn 2 S 4 (ZIS) is one of the most promising photocatalysts with an adjustable band gap (2.06-2.85 eV) for visible light absorption.…”
mentioning
confidence: 99%
“…† The lattice spacings of 0.32 and 0.25 nm are assigned to the (102) plane of ZIS and the (111) plane of MoC, respectively, demonstrating the successful combination of ZIS and MoC@NG via the in situ solvothermal method. 37,38 The STEM-EDS (scan transmission electron microscopy-energy dispersive spectroscopy) images further conrm the good coupling of ZIS and MoC@NG and suggest the uniform distribution of Zn, In, S, Mo and N elements (Fig. 1g).…”
Section: Materials Characterizationmentioning
confidence: 82%